Incredible mollusks - Townsend, John, 1955- (Freestyle express, 2006)
Provides an introduction to the world of mollusks, introducing various types of mollusks, including slugs, snails, and oysters, discussing how they breathe, feed, reproduce, and defend themselves, and looking at threats to their survival.